Factors associated with hand, foot and mouth disease (HFMD) outbreak cases in Kelantan 2018 - Ismail, Nur Akmal (2020)
Background: Hand, foot and mouth disease (HFMD) remains a significant public health concern worldwide, especially in the Western Pacific Region. In Malaysia, the Ministry of Health (MOH) had adopted the HFMD surveillance system, guideline, prevention and control program for managing the HFMD cases and outbreak occurrence at any level. However, there are still high cases of HFMD and outbreak occurrence reported despite these control program had been made. Therefore, it is vital to recognise the factor associated with the HFMD outbreak cases to overcome this problem. Objective: This research aims to describe characteristics of HFMD cases, the proportion of HFMD outbreak cases and to study the associated factors of HFMD outbreak cases in Kelantan state in 2018. Methodology: This study consists of two parts. Part I adopted the descriptive cross-sectional study while in Part II, the comparative cross-sectional study design was used. The data of HFMD patients in Kelantan in 2018 were using the secondary data obtained from Communicable Disease Control (CDC), Unit Kelantan State Health Department. Results: More than half of HFMD cases in Kelantan in 2018 were aged 5 years and above (53.1%) and male group (55.8%). Majority of them were Malays (96.4%), resided in rural areas (78.6%) and had been treated as outpatients (95.4%). Many of them attended kindergarten (38.3%) followed by others such as home care and different working places (27.1%), school (18.2%) and nursery (16.4%). Notified HFMD cases also more concentrated during warm weather season between May and August (40.9%). Among 1026 HFMD patients, 70 patients were HFMD outbreak cases, equivalent to 6.8%. The significant association found between HFMD outbreak cases among children aged less than 5 years old were those who attended the kindergarten (Adj. OR 0.330; 95% CI: 0.114, 0.957, p-value=0.041) and were taken care at home (Adj. OR 0.008; 95% CI: 0.001, 0.067, p-value<0.001) compared to those who attended the nursery and the disease occurred during the warm season (Adj. OR 0.154; 95% CI: 0.043, 0.557, p-value=0.004) compared to the rainy season. Conclusion: This study reported that the significant factors associated with HFMD outbreak cases in Kelantan among the children below than 5 years were the children who attended the kindergarten, home-care children and disease occurred during the warm season. Therefore, we recommend the collaboration of multi agencies to continuously monitor and improvise the current particular program related to HFMD in nurseries, kindergartens and schools to improve knowledge, attitude and practice among institution managers, teachers and staff towards HFMD. Other than that, we also suggest to develop targetted interventions including early detection of disease, improve the environmental hygiene, effective gatekeeping and good practice in preparation of food in daycare centres to reduce the incidence and burden of the outbreaks.